An Effectiveway to Improve Problem Solving Skill Using TPS, T24S and T21S:A Comparative Study - Dol, Sunita M.; Halkude, S. A. (Journal of Engineering Education Transformations, 2017)
While studying various engineering courses, we often come across two types of problem statements: Simple problems which are possible to solve within two steps where as Complex one are those which required more than two steps to solve. Further in complex type of problem statement, there are two types: Type 1- Complexity is less initially and increases as we proceed further and Type 2- Complexity is more initially and it decreases for further steps. In the present study, we considered the active learning strategies to solve these types of problem statement. For this study, Theory of Computation course of Second Year Computer Science and Engineering is considered. Think-Pair- Share (TPS) is a well known active learning strategy in which students work on a problem posed by instructor, first individually (Think), then in pairs (Pair) and finally together with the entire class (Share).TPS is considered for Simple type of problem statement. After implementing TPS frequently, we have modified the TPS activity in such a way that it can be used to solve the Type1 and Type2 problem statements as mentioned above. The modified active learning strategies are renamed T24S (Think-Pair- Four in Group-Share) and T21S (Team-Pair- Individual-Share). T24S consist of four phases- Think, Pair, Four in group and Share phase. In phase "four in group phase", two pairwork together to complete the task. So this T24S activity is considered to solve the Type1 examples. I n T 2 1 S , students work in the group of four to solve the problem statement. Next, teams split into pair to work on the same problem statement. Finally pair breaks up and student work individually to complete the task followed by sharing of the problem statement solution with the class. Such T21S activity is employed for solving the Type 2 problem statements.We conducted pre-post single group study for three learning objectives (LOs) as (1) solve the simple problem statement (LO1), (2) solve the complex problem statement of Type1 (LO2) and (3) solve the complex problem statement of Type2 (LO3). It is found that TPS, T24S and T21S methods are useful for satisfying LO1, LO2 and LO3 respectively.The objective of this study is to improve the problem solving skill of students. In this study, we are presenting the results obtained along with feedback about TPS, T24S and T21S.